Determining the Moisture and Plant Effect on Nutrient Release, and Plant Nutrient Uptake Using Ion Exchange Resin Membrane. Issue 7 (12th April 2018) - Ghosh, Upasana; Chatterjee, Amitava; Bremer, Eric
ABSTRACT: Traditional soil testing has a limited predictability about available nutrients for plant uptake. Potential of ion exchange resin membrane (RM) or plant root simulator probe is evaluated to determine the effect of moisture on nutrient availability and uptake by corn ( Zea mays L.), under greenhouse condition. Available nutrient concentrations measured by RM in two soil series at three soil moisture levels (40%, 60%, and 80% of field capacity) with (W) and without (W/O) the plant at V3 and V7 stages were compared with plant nutrient content at the V7 stage. Soil moisture did not influence RM-extracted nutrient concentrations (except for N at V3). Concentrations of nitrogen (N), phosphorus (P), potassium (K), sulfur (S), and iron (Fe) from RM at the V3 stage significantly correlated with shoot uptake. The presence of plant (W- vs. W/O-plant) significantly influenced RM-nutrient concentration at both stages. RM can predict crop nutrient requirements. Abbreviations: Ion exchange resin membrane (RM); nitrogen (N); phosphorus (P); potassium (K), sulfur (S), field capacity (FC)